Finite Groups with System of SE-Supplemented Subgroups - Xiaolan, Yi; Shemetkova, O. L. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
We study the influence of the properties of supplemented subgroups on the structure of finite groups. The conditions under which a normal subgroup of a finite group possesses cyclic chief p-factors are obtained.